Ammonia ion selective electrode and indophenol methods can be used successfully to evaluate meat contaminated by ammonia - F. Hijaz; J. Scott Smith; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 2007)
Anhydrous ammonia is used as a refrigerant in large warehouses for cooling meats, fruits, vegetables, milk, and other products. Ammonia offers several advantages over other refrigerants; it does not harm the ozone layer and is a very efficient heat transfer agent. However, cold storage facilities sometimes have ammonia leaks. When this happens, products are held for an indeterminate period or are condemned because there is no official method to evaluate the degree of product contamination. In one case, a warehouse owner discarded a product because he could not prove that it was safe. His insurance company would not compensate him because he failed to prove that the product was not safe for human consumption. Over the last several years, many owners of refrigeration warehouses have experienced this problem. Foodborne illness outbreaks caused by ammonia have been reported twice in the United States. On October 30, 1985, a foodborne outbreak was reported in two elementary school children in Wisconsin. The children suffered from burning of the mouth and throat, as well as nausea, within one hour of drinking milk packaged in half-pint containers. Analysis of the remaining containers revealed that the milk was contaminated with ammonia at levels ranging from 530 ppm to 1,524 ppm. The pH levels of the contaminated milk ranged from 9.1 to 10.0, while normal milk pH ranges from 6.7-6.9. This was the first reported incident of acute ammonia poisoning by the Centers for Disease Control and Prevention. On November 25, 2002, another outbreak was reported in several dozen school children in Illinois. The children suffered from stomachache, nausea, and headache within one hour of eating chicken tenders. A laboratory investigation by the U.S. Department of Agriculture=s Food Safety Inspection Service (FSIS) showed that the chicken tenders were contaminated with ammonia at levels ranging from 552 ppm to 2,468 ppm. Assessment of ammonia damage to determine whether food is fit for human consumption is based on tentative methods because published information is limited. According to the Food and Drug Administration (FDA), at least three different measurement methods should be used to assess contaminated products: ammoniacal nitrogen, sensory test, and pH measurement. The objective of this study was to evaluate assays for ammonia detection so that they could be used for rapid in-plant testing of meat contaminated by ammonia refrigerant leaks and to determine the ammonia background of different meat products using the ammonia ion selective electrode (ISE).
Keywords: Cattlemen' s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; Ammonia ion; Indophenol